2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--29195
|View full text |Cite
|
Sign up to set email alerts
|

Year Three: Analysis of 3D technology impact on STEM based courses; specifically introduction to engineering courses.

Abstract: oped over 5 new courses, including UTEP technology & society core curriculum classes specifically for incoming freshman with a STEM background. Dr. Perez was awarded the 2014 "University of Texas at El Paso award for Outstanding Teaching". Dr. Perez has thirteen years of professional experience working as an Electrical and Computer Engineer. leads a team to provide technical support to faculty and students utilizing UGLC classrooms and auditoriums. Dr. Perez is committed to the highest level of service to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Through designing 3D models, prototypes and drawing, students could scaffold their geometric understandings and use 3D printing to express ideas, create solutions, and solve authentic problems (e.g., Ng & Chan, 2021;Chiriacescu et al, 2021;Dickson et al, 2021). In addition, seven other studies developed students' other mathematical concepts including multivariable calculus (Medina Herrera et al, 2019;Paul, 2018), matrix and vector (Walentyn ́ski et al, 2021), polynomial (El Bedewy et al, 2021a), and engineering-related topics (e.g., principles behind 3D printing) (Anastasiou et al, 2013;Lin et al, 2018;Perez et al, 2016). These four studies were conducted at the higher education level.…”
Section: Collaborative Learningmentioning
confidence: 99%
“…Through designing 3D models, prototypes and drawing, students could scaffold their geometric understandings and use 3D printing to express ideas, create solutions, and solve authentic problems (e.g., Ng & Chan, 2021;Chiriacescu et al, 2021;Dickson et al, 2021). In addition, seven other studies developed students' other mathematical concepts including multivariable calculus (Medina Herrera et al, 2019;Paul, 2018), matrix and vector (Walentyn ́ski et al, 2021), polynomial (El Bedewy et al, 2021a), and engineering-related topics (e.g., principles behind 3D printing) (Anastasiou et al, 2013;Lin et al, 2018;Perez et al, 2016). These four studies were conducted at the higher education level.…”
Section: Collaborative Learningmentioning
confidence: 99%
“…lately tablets have started to claim their places in classrooms (Perez, Gonzalez, Pitcher & Golding [2]). …”
Section: Introductionmentioning
confidence: 99%
“…[2] found that different and is woven into all the times and places of students" lives. Desktop technologies and landline phones are about buildings; mobile devices are about people.…”
Section: Introductionmentioning
confidence: 99%